2019
DOI: 10.6026/97320630015189
|View full text |Cite
|
Sign up to set email alerts
|

Impact of omega-3 fatty acids on calorie intake and certain anthropometric measurements in children with sickle cell disease in Saudi Arabia

Abstract: The nutritional status and growth in children with sickle cell disease is compromised due to intake of diet that is low in calories as well as deficient in nutrients. Growth stunting and a low body mass index have been observed in these children. Some children exhibit pica, which is an abnormal eating pattern by ingesting things other than food, like paper, wood etc. This also was found to correlate to lower hemoglobin values. Interventions with certain essential nutrients such as omega-3 fatty acids are known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…This review found that the supplementation of PUFAs, especially omega-3 FAs among children with sickle cell disease (SCD) was expected to improve their nutrition and growth parameters which is important because these children are more likely to suffer from malnutrition, which results in stunted growth and increases the severity of anaemia . This can be proven by a study conducted among SCD children showing that the supplementation of omega-3 FAs for six months significantly improve their haemoglobin percentage, BMI and body fat percent (13). Apart from that, this findings was consistent with previous findings showing that supplementing SCD patients with necessary omega-3 fatty acids reduces anaemia, vaso-occlusive pain episodes, white blood cell count, and pro-thrombotic activity (49).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This review found that the supplementation of PUFAs, especially omega-3 FAs among children with sickle cell disease (SCD) was expected to improve their nutrition and growth parameters which is important because these children are more likely to suffer from malnutrition, which results in stunted growth and increases the severity of anaemia . This can be proven by a study conducted among SCD children showing that the supplementation of omega-3 FAs for six months significantly improve their haemoglobin percentage, BMI and body fat percent (13). Apart from that, this findings was consistent with previous findings showing that supplementing SCD patients with necessary omega-3 fatty acids reduces anaemia, vaso-occlusive pain episodes, white blood cell count, and pro-thrombotic activity (49).…”
Section: Discussionsupporting
confidence: 84%
“…In contrast, two studies reported no significant effects of PUFA supplementation on body weight (22,23). Furthermore, improvement in haemoglobin, nutrition, physical health and growth parameters such as body mass index (BMI) and body fat percentage was all related to the intake of PUFA (6,13). Olsen et al reported that PUFA status, particularly n-3LC-PUFAs, were associated with better development scores based on Malawi Development Assessment Tool (MDAT) z-scores among malnourished children with higher mid-upper arm circumference, more fat-free mass, better anthropometric measurement and iron status.…”
Section: Growthmentioning
confidence: 98%
See 1 more Smart Citation
“…This study also showed a significant relationship of p=0.000 (p<0.05) between the adequacy of omega-3 consumption and the incidence of wasting. This is supported by the research of Shahida Khan et al, 30 which in their research mentioned that omega-3 supplementation increased the amount of energy consumed to improve the nutritional status of the respondents of the study.…”
Section: Relationship Between Omega-3 Intake and The Incidence Of Stu...mentioning
confidence: 59%